High performance servers. (Architecture Technology Corporation, 1991)
Please note this is a Short Discount publication. LANs have gone through stages. Early LANs connected asychronous terminals to minicomputers. With the advent of the IBM PC the focus on technology changed to that of PCs connected to some type of 'file server'. After a number of years, the battle over file servers turned into a battle of network operating systems. With the advent of the client server model, and high performance workstations, one direction the battle has been taking is to develop a high performance server engine. The general strategy in this arena is to attempt to remove bot.